Sanksi Hukum Bagi Anak Sebagai Pelaku Tindak Pidana Pencurian Dengan Kekerasan (Studi Kasus Putusan Nomor: 25/Pid.Sus-Anak/2021/Pn Bks) - Restu Fauzi; Mukhlis Al Huda; Muhammad Rizal Rustam (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Children are part of the younger generation as one of the human resources that hasa strategic role and has special characteristics and traits. The Law on Juvenile Courts is considered no longer appropriate to protect children's rights before the law. The writing of this study aims to determine the application of legal sanctions for children as perpetrators of the crime of theft with violence and analyze the Judge's Decision for Children as Perpetrators of Violent Theft (Case Study of Decision Number: 25/Pid.Sus-Anak/2021/PN Bks). The method used in this research uses the Normative Research Method, namely research whose object of study includes norms or basic rules, legal principles, laws and regulations, comparative law, doctrine, and jurisprudence. The type of data used is secondary data, namely data obtained from literature (library research). This research is descriptive Analytical. In this case the defendant was 17 years old, Child in Conflict with the Law ANDIKA PRATAMA Alias DIKA Bin M. SURON, had committed. Theft with violence against persons as regulated and punishable in the indictment by Noting, Article 365 paragraph (2) 1st and 2nd of the Criminal Code and Law Number 11 of 2012 concerning the Criminal Justice System for Children Against the Law and Law Number 8 of 1981 concerning Criminal Procedure Law and other relevant laws and regulations violating Article 365 paragraph (2) 1st and 2nd of the Criminal Code.